(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Abstract Background: Limestone is widely spread in nature and constitutes about (20-25%) of the total sedimentary rocks [1]. It is ranked third globally from mineral sources and extracted rocks [2]. Limestone represents the large ratio of the stratified column of Iraq [3]. Materials and Methods: This study involves the evaluation of limestone rocks as construction materials of Al- Nfayil formation in Bahr Al-Najaf Depression by 15 stations distributed over a region. The research includes field and laboratory aspects. Results: Through the tests, the viability of limestone for construction purposes was determined. As it is suitable for construction because it succeeded the requirements of the building standard (ASTM, C568, 2004), and did not succeed in the requirements of the standard for railway control aggregates (O.R.B.D, 1999, Raymond, 1979). The study recommends estimating and calculating the amount of reserves of limestone rocks available in the study area for the purpose of calculating economic feasibility